Core stability as a risk factor for the development of acute lower extremity injuries in an athletic population: a prospective study - Blaiser, C.; Ridder, R.; Willems, T.; Vermeulen, S.; Danneels, L.; Roosen, P. (British Journal of Sports Medicine, 2021)
Background Impaired core stability has been suggested to influence lower extremity functioning and might contribute to the development of acute lower extremity injuries. Prospective studies that examine this relationship are currently lacking.